Karakteristik Sifat Kimia Tanah Ultisol pada Tanaman Karet di Desa Kersik Belantian Kecamatan Jelimpo Kabupaten Landak - Goreti, Valentina; Nusantara, Rossie Wiedya; Manurung, Rinto (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2026)
Rubber is one of the agricultural commodities that plays a very important role, both as a source of income, employment opportunities, and a source of foreign exchange for the country. Rubber plants have a very high economic value, this annual plant can be tapped for its rubber sap for the first time at the age of 5 years, land for growing rubber plants generally pays more attention to physical properties than chemical properties. This study aims to determine the characteristics of the chemical properties of ultisol soil in rubber plants in the village of Kersik Belantian, Jelimpo District, Landak Regency. Determination of observation points was carried out using the diagonal method, determination of coordinate points using the Global Positioning System (GPS). The results showed that the pH of the superior rubber soil was 4.78 (acidic) and local rubber 4.90 (acidic). Organic carbon of superior rubber soil was 3.78% (high) and local rubber 0.20% (very low). Total nitrogen of superior rubber soil was 0.35% (moderate) and local rubber 0.44% (moderate). Available phosphorus in superior rubber soil is 15.23 ppm (low) and local rubber is 11.23 ppm (low). Potassium-dd in superior rubber soil is 0.12 cmol (+)kg-1 (very low) and local rubber is 0.14 cmol(+)kg-1 (very low). Cation exchange capacity of superior rubber is 16.49 cmol (+)kg-1 (low) and local rubber is 12.80 cmol(+)kg-1 (low). Base saturation of superior rubber is 4.24% (very low) and local rubber is 5.16% (very low). Al-dd in superior rubber is 0.98% (low) and local rubber is 0.89% (very low). Keyword: Chemical Properties, Ultisol Soil, Rubber, Soil Characteristics